DETERMINAN MINAT MENABUNG MASYARAKAT PADA BSI KCP RATULANGI PALOPO DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI (STUDI KASUS MASYARAKAT KOTA PALOPO - Aulia, Aulia (Institut Agama Islam Negeri Palopo, 2023)
This study aims to find out whether knowledge, promotion, facilities, and location factors affect people's interest in saving at BSI KCP Ratulangi Palopo. And whether religiosity as a mederation variable can strengthen/increase the factors of knowledge, promotion, facilities and location on the interest in saving. This type of research is quantitative descriptive. The data collection technique in this study uses a questionnaire/questionnaire, which is distributed online to the people of Palopo City who use Sharia banks. The results of the study showed that the variables of knowledge had no effect on interest in saving while the variables of promotion, facilities, and location had a significant effect on interest in saving and religiosity moderated the variables of knowledge, promotion, facilities, and location on interest in saving at BSI KCP Ratulangi Palopo. Keywords: Knowledge, promotion, facilities, location, religion, interest in saving.